Um estudo computacional do efeito da compactação dos condutores sobre o campo elétrico em arranjos de linhas aéreas de transmissão - Adilton Junio Ladeira Pereira (2023)
Compact AC overhead transmission power lines provide higher transmission levels, for a given right of way, because of the proposal to reduce distances between phases and expand conductor bundles. On the other hand, the electric field on the surface of conductors, insulators and hardware are significantly accentuated in these configurations, resulting in a more careful assessment of the impacts associated with the corona effect. For this reason, to meet the requirements related to electromagnetic emission, the technical conformity of the projects needs to be attested by carrying out indoor laboratory tests. In the case of hardware and insulators sets, it is verified, among other requirements, the voltage level for the onset and extinction of the visual corona effect and the value of the Radio Interference Voltage. Due to the limitations of technical, financial and space resources, these tests are carried out, for the most part, in closed laboratory environments through a single-phase reproduction of the transmission system. Faced with this situation, a problem to be investigated concerns the equivalence between the electric field values verified on the surfaces of the conductors for the installation condition of the single-phase reproduction in the laboratory and the operating condition of the TL in a three-phase environment. For a transmission system with an arrangement of adjacent phases, as is the case with compact lines of 500 using Cross-Rope type structures, the single-phase test arrangement must incorporate the effect of the conductors of adjacent phases. According to the normative procedure, this shielding effect is simulated through the installation of reflection planes with predetermined clearance. With the aim of evaluating the influence of adjacent phases and their correlation with the maximum levels of electric field, this dissertation presents sensitivity studies of single-phase reproduction taken as a function of the test voltage and the clearance of reflection planes. Using the COMSOL Multiphysics® environment, the results show that a single test voltage is not able to guarantee correspondence for all subconductors in the conductor bundle. Furthermore, the reflection planes of the reflective panels can alter the electric field levels on the surface of subconductors in the order of 13%.